Cancer neoepitopes for immunotherapy: discordance between tumor-infiltrating T cell reactivity and tumor MHC peptidome display - Wickström, Stina L.; Lövgren, Tanja; Volkmar, Michael; Reinhold, Bruce; Duke-Cohan, Jonathan S.; Hartmann, Laura; Rebmann, Janina; Mueller, Anja; Melief, Jeroen; Maas, Roeltje; Ligtenberg, Maarten; Hansson, Johan; et al. (Frontiers in immunology, 2019)
Tumor-infiltrating lymphocytes (TIL) are considered enriched for T cells recognizing shared tumor-antigens or mutation-derived neoepitopes. We performed exome sequencing and HLA-A*02:01 epitope prediction from tumor cell lines from two HLA-A2 positive melanoma patients whose TIL displayed strong tumor reactivity. The potential neoepitopes were screened for recognition using autologous TIL by immunological assays and presentation on tumor major histocompatibility complex class I (MHC -I) molecules by Poisson detection mass spectrometry (MS). TIL from the patients recognized 5/181 and 3/49 of the predicted neoepitopes, respectively. MS-screening detected 3/181 neoepitopes on tumor MHC I from the first patient but only one was also among those recognized by TIL. Consequently, TIL enriched for neoepitope-specificity failed to recognize tumor cells, despite being activated by peptides. For the second patient, only after IFN-γ treatment of the tumor cells was one of 49 predicted neoepitopes detected by MS and this coincided with recognition by TIL sorted for the same specificity. Importantly, specific T cells could be expanded from patient and donor peripheral blood mononuclear cells (PBMC) for all neoepitopes recognized by TIL and/or detected on tumor MHC I. In summary, stimulating the appropriate inflammatory environment within tumors may promote neoepitope MHC-presentation while expanding T cells in blood may circumvent lack of specific TIL. The discordance in detection between physical and functional methods revealed here can be rationalized and used to improve neoantigen-targeted T cell immunotherapy.
Gesehen am 24.01.2020